Shape Coexistence In The Neutron-Deficient Lead Isotopes, As Seen From Within Complimentary Models - Fossion, Ruben; Lalazissis, G. A. (HNPS Advances in Nuclear Physics, 2019)
In the neutron-deficient lead isotopes, at low excitation energies, the nucleus does not have one preferred excitation mode. Instead, three different coexisting "families" of excitation states are found in the excitation spectrum. Theoretical approaches are offered within the mean-field models (both relativistic and non-relativistic) and within the Interacting Boson Model (IBM). Recently, a third approach using bosoncoherent states has shown to offer a possible bridge between the former two approaches.